Growth and Photovoltaic Properties of High-Quality GaAs Nanowires Prepared by the Two-Source CVD Method - Wang, Ying (Nanoscale Res Lett, 2016)
Growing high-quality and low-cost GaAs nanowires (NWs) as well as fabricating high-performance NW solar cells by facile means is an important development towards the cost-effective next-generation photovoltaics. In this work, highly crystalline, dense, and long GaAs NWs are successfully synthesized using a two-source method on non-crystalline SiO(2) substrates by a simple solid-source chemical vapor deposition method. The high V/III ratio and precursor concentration enabled by this two-source configuration can significantly benefit the NW growth and suppress the crystal defect formation as compared with the conventional one-source system. Since less NW crystal defects would contribute fewer electrons being trapped by the surface oxides, the p-type conductivity is then greatly enhanced as revealed by the electrical characterization of fabricated NW devices. Furthermore, the individual single NW and high-density NW parallel arrays achieved by contact printing can be effectively fabricated into Schottky barrier solar cells simply by employing asymmetric Ni-Al contacts, along with an open circuit voltage of ~0.3 V. All these results indicate the technological promise of these high-quality two-source grown GaAs NWs, especially for the realization of facile Schottky solar cells utilizing the asymmetric Ni-Al contact. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s11671-016-1420-y) contains supplementary material, which is available to authorized users.